Spinach production in cocopeat: Effects of soil block number and the number of emitters on plant growth, nitrate concentration, and antioxidant activity - Machado, RMA (2019)
Currently, the interest in the use of coir dust (or cocopeat) as a growing medium has increased. The aim of this research was to evaluate the effects of plant density and the number of emitters per Styrofoam box on plant growth, nitrate (NO3-) concentration and antioxidant activity in spinach (Spinacia oleracea L. cv. Manatee) cultivated in cocopeat. The experiment was carried out with four treatments, including two plant densities (160 and 280 plants/m2) and two number of emitters per Styrofoam box (4 and 8 emitters). The crop was irrigated and fertigated daily with a complete nutrient solution, in which NO3-/NH4+ ratio decreased through the crop cycle. Shoot dry weight was not affected by plant density or emitter number. However, the yield (kg m-2) increased significantly with plant density and with the number of the emitters by Styrofoam box. The yield in treatment 280 plants/m2 and 8 emitters reached 5.4 kg m-2. Leaf-blade and petiole NO3- concentration was not affected by plant density, number of emitters and the interaction between treatments. Leafblade and petiole NO3- concentration was low, ranged from 0.49 to 0.56 and 0.94 to 0.96 NO3- mg g-1 fresh weight, respectively. These results indicate that cocopeat is a very suitable growing medium for spinach production.